Not so special an investigative study on selected national special education school in the Philippines - Bacani, Emmanuel Louis Mendiola (2012)
"This study proves the insufficiency of the budget allocated to special education (SPED) schools in the country which cater to the children with special needs (CSN). Using the Structural-Functionalism Theory and Weber's Theory of Bureaucracy as framework, the study examines the government's dysfunctions - the undesirable outcomes of its operations - in its failure in addressing the news of CSNs and of the SPED schools, particularly their need for adequate funds. With documentary evidence and interviews from the teachers and staff of three national SPED schools and of a SPED Center, this investigation exposes how the lack of funds and of a significant budget increase has caused the problematic conditions off the schools: lack of adequate books, materials, classrooms, facilities and even teachers for the education of the special children. This research also reveals the perception of SPED officials and experts regarding the many issues of the country's SPED sector such as the low number of enrolled CSNs. Lastly, this study also examines the failure of the Philippines Congress to uplift the SPED sector by passing a comprehensive SPED law which could address the budget dilemmas of the special schools - institutions that appear to be "not so special" for the government."